The Effect of Educational Socialization Using Poster Media on Understanding the Proportion of Calories for Children - Shinta Zahra Zahriyatul Khamsah; Asep Bayu Dani Nandiyanto (ASEAN Journal of Science and Engineering Education, 2024)
The purpose of this study was to provide an understanding to the community in Parongpong, Indonesia, about the importance of calorie intake in children's bodies. nutrition remains balanced. The research subjects took a sample of 15 people from Cigugur Girang consisting of 2 men and 13 women. The method used is to do a pre-test and post-test using google form on the people of Cigugur Girang. The results of this study obtained an average N-Gain score of 73% and an increase in score of 38% with a minimum pre-test score of 180 and a maximum of 200, while a post-test score of at least 60 and a maximum of 150. The use of poster media is quite effective in educating the people of Cigugur Girang. These results were obtained because the community was not too familiar with calorie intake, although some already understood it, some others had a very small pre-test score with a score of only 60, after counseling with poster media, the Cigugur Girang community understood more about calorie intake marked with an increase in the value of pre-test to post-test by 38%. The people of Cigugur Girang can understand the importance of calorie intake for children to avoid calorie deficiency or excess disease.